Type specimens of Ichneumonidae (Hymenoptera) described by Brèthes held in the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”, Argentina - Onody, Helena Carolina; Brandão, Carlos Roberto Ferreira; Mulieri, Pablo Ricardo (Zootaxa, 2021)
A catalogue is provided for the name-bearing type specimens of Ichneumonidae described by Brèthes held in the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”. The collection includes a total of six holotypes, 16 lectotypes, and 43 paralectotypes, of 22 nominal species.